Current research on anti-breast cancer synthetic compounds. Issue 8 (24th January 2018) - Liu, Jia; Ming, Bian; Gong, Guo-Hua; Wang, Di; Bao, Gui-Lan; Yu, Li-Jun
Abstract : Breast cancer (BC) is the most common cancer for females and its incidence tends to increase year by year. Abstract : Breast cancer (BC) is the most common cancer for females and its incidence tends to increase year by year. Currently, the backbone of therapy for BC is mainly chemotherapy, however its toxicity in normal cells and acquired tumor resistance to the drug used are considered as the main barriers. Therefore, there is still an urgent need for the development of more effective and safer anti-BC agents. Based on previous reference documents in recent years, this review covers the work reported on the anti-BC compounds which are classified according to the structures. This review summarized 185 significant anti-BC compounds which are classified by functional groups according to the animal model data, although there would be some limitations with the data. This review highlights the properties of new compounds endowed with promising anti-BC properties, which may be proven to be more effective and selective, and possibly free of unwanted side effects. The reviewed compounds represent an interesting possibility to overcome BC and to reduce the percentage of patients with a poor response to drug therapy.